Prevention of Sand Theft Based on RSSI Based Relative Positioning and Tracking Approach - M, Shyam; R, Giriharan; P, Hariprasath; D, Kirankumar (2023 International Conference on Circuit Power and Computing Technologies (ICCPCT), 2023)
There are numerous areas that require an absolute solution to their technical issues. Sand theft prevention is the subject of this study. The world is filled with technology that can be explored, directed towards our field, and result in a fully developed process flow. This paper presents a better approach of using a hardware kit to monitor inside activities which is taking place in the sand mining area located nearby to bank-shore area [10]. Using RSSI Technology, this application is used to stop impending sand theft attacks. Insider SAND theft attacks cannot be stopped by standard security measures such as encrypting - decrypting. This paper outlines a strategy for thwarting insider data theft attacks using a specific tracking technology. The technology in this case is carried out by building a prototype based on a web pattern, validating the efficacy of the technology. This application senses unauthorised access, thereby raising various alerts and thwarts on suspects, aimed at ceasing any attempt of theft. Thus, insider theft is prevented.